2016
DOI: 10.1038/hdy.2016.46
|View full text |Cite
|
Sign up to set email alerts
|

Complementary sex determination, inbreeding depression and inbreeding avoidance in a gregarious sawfly

Abstract: Although most Hymenoptera reproduce via arrhenotokous haplodiploidy, the underlying genetic mechanisms vary. Of these, the most widespread mechanism appears to be single-locus complementary sex determination (sl-CSD), in which individuals that are diploid and heterozygous at a sex-determining locus are female, and individuals that are homozygous or hemizygous are male. Because inbreeding increases the probability of producing diploid males, which are often sterile or inviable, sl-CSD can generate substantial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 46 publications
(83 reference statements)
0
43
0
Order By: Relevance
“…We collected cocoons as they were spun and stored them in individual gelatin capsules until adult emergence. We maintained all larvae and cocoons at 22  ° C, 70% relative humidity, and an 18–6 h light-dark cycle [40, 46]. Upon emergence, live adults were stored at 4  ° C until needed for crosses, morphological measurements, or behavioral assays.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We collected cocoons as they were spun and stored them in individual gelatin capsules until adult emergence. We maintained all larvae and cocoons at 22  ° C, 70% relative humidity, and an 18–6 h light-dark cycle [40, 46]. Upon emergence, live adults were stored at 4  ° C until needed for crosses, morphological measurements, or behavioral assays.…”
Section: Methodsmentioning
confidence: 99%
“…We first placed females in a clear 3.25-ounce deli cup with a single male until mating occurred. Neodiprion , like most hymenopterans, have arrhenotokous haplodiploidy, in which unfertilized eggs develop into haploid males [46, 52]. Although both mated and unmated females will oviposit readily ( personal observation ), we used mated females in our N. lecontei/N.…”
Section: Methodsmentioning
confidence: 99%
“…not affecting protein sequence) and so far there is no evidence for paralogous NaK and TPI genes at least in sawflies, these polymorphic sites might indicate heterozygosity because of diploidy. This can happen if there is no heterozygosity at the complementary sex determination (CSD) locus, preventing female development from a diploid embryo (Naito and Suzuki 1991, Heimpel and de Boer 2008, Harper et al 2016. Survival of diploid males is known in sawflies (Naito and Suzuki 1991, Cook et al 2013, Harper et al 2016 and is common in nature at least in some species of Apocrita (Liebert et al 2005, Retamal et al 2016.…”
Section: Possible Diploid Malesmentioning
confidence: 99%
“…These observations suggest that, when it comes to forming and maintaining larval aggregations, larvae do not discriminate between kin and nonkin (Figure ). These findings cannot be explained by a lack of capacity for kin recognition in this species because previous work has shown that adults do discriminate between related and unrelated mates (Harper et al., ). One possible implication of our results is that individuals derive sufficient direct benefits from aggregating that kin selection need not be invoked to explain the evolution and maintenance of larval gregariousness.…”
Section: Discussionmentioning
confidence: 66%